Mekanisme Pemungutan dan Pengenaan Pajak Penghasilan Pasal 21 dengan Berlakunya PMK 168 Tahun 2023 - Triatmoko, Hanung; Karunia, Asaprima Putra; Endiramurti, Saktiana Rizki; Salim, Meka Sabilla (Jurnal Akuntansi dan Pajak, 2024)
This research aims to determine the impact of implementing PMK 168 of 2023 for employees who receive income and for employers. The research method used is a quantitative method. The analysis technique was carried out by simulating the calculation of PPh article 21 before and after the implementation of PMK 168 in 2023. The results of the research showed that the implementation of the calculation of PPh article 21 using TER did not affect the total PPh21 burden on employees but did affect the monthly revenue pattern. The impact for employers is the possibility of having to refund PPh 21 employees who are overpaid.